The supreme constitutional court constitutional judgments regarding some provisions of law no.11/1991 concerning the general sales tax and law no. 79/1975 concerning the social insurance = أحكام دستورية بشأن بعض مواد القانون رقم 11 لسنة 1991 بشأن الضريبة العامة على المبيعات والقانون رقم 79 لسنة 1975 بشأن التأمينات الاجتماعية / the Supreme Constitutional Court. - Egypt. the Supreme Constitutional Court (2025)
In the name of the people the supreme constitutional court in the public session held on Sunday the 7th of April =, 2013 corresponding to the twenty sixth of jumada first, 1434 Islamic calendar باسم الشعب المحكمة الدستورية العليا بالجلسة العلنية المنعقدة يوم الاحد السابع من ابريل سنة 2013م ، الموافق السادس والعشرين من جمادى الاول سنة 1434 ه